Collaboration Between The Regional Government, Local Msmes, And Local Influencers In Maximizing Jambi's Economic Potential - Heppi Syofya; Novic Diwi Pernanda (Yayasan Inovasi Kemajuan Intelektual, 2023)
Jambi Province has significant economic potential, particularly in agribusiness, cultural and nature-based tourism, and the unique products of local Micro, Small, and Medium Enterprises (MSMEs). However, this potential is often not optimally utilized due to classic challenges in terms of market penetration, weak digital branding, and coordination between stakeholders. This study analyzes the urgency and effectiveness of the Collaborative Triple Helix model involving the Regional Government (Regulator and Facilitator), Local MSMEs (Producers), and Local Influencers (Digital Marketing Catalysts) in creating a synergistic and sustainable economic ecosystem in Jambi. The main objectives of this study are to identify the most effective collaboration mechanisms to (1) increase the exposure of Jambi products and destinations through social media, (2) strengthen the branding capabilities of MSMEs, and (3) increase sales volume and tourist visits. Using a qualitative-descriptive approach involving in-depth interviews with representatives of the three parties, this study proposes a digital platform-based collaboration model. Initial findings indicate that local influencers play a crucial role as a bridge of trust between MSME products and millennial/Gen Z audiences. In contrast, local governments must shift from mere regulation to a digital incubator and cross-sectoral coordinator. The conclusion emphasizes that intensifying this collaboration is key to accelerating Jambi's digital economy.